Toxicity overview of endocrine disrupting chemicals interacting in vitro with the oestrogen receptor - Alva-Gallegos, Raul; Carazo, Alejandro; Mladěnka, Přemysl (Environmental toxicology and pharmacology, 2023)
The oestrogen receptor (ER) from the nuclear receptor family is involved in different physiological processes, which can be affected by multiple xenobiotics. Some of these compounds, such as bisphenols, pesticides, and phthalates, are widespread as consequence of human activities and are commonly present also in human organism. Xenobiotics able to interact with ER and trigger a hormone-like response, are known as endocrine disruptors. In this review, we aim to summarize the available knowledge on products derived from human industrial activity and other xenobiotics reported to interact with ER. ER-disrupting chemicals behave differently towards oestrogen-dependent cell lines than endogenous oestradiol. In low concentrations, they stimulate proliferation, whereas at higher concentrations, are toxic to cells. In addition, most of the knowledge on the topic is based on individual compound testing, and only a few studies assess xenobiotic combinations, which better resemble real circumstances. Confirmation from in vivo models is lacking also.
Keywords: Receptors, Estrogen; xenobiotika; Endocrine Disruptors; endokrinní disruptory; estrogeny; lidé; Estradiol; Estrogens; Xenobiotics; receptory pro estrogeny; estradiol; Humans